Pengaruh Penerimaan Pajak Dan Defisit Anggaran, Terhadap Pertumbuhan Ekonomi Di Negara BRICS - Davanie Milhatin Sirfa; Nairobi; Arif Darmawan (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to analyze the effect of budget deficit, tax revenue, and labor force participation rate on economic growth in BRICS countries (Brazil, Russia, India, China, and South Africa). Using a quantitative approach with panel data from 2014 to 2023, the analysis was conducted through regression models using the Random Effect Model approach. The results indicate that the budget deficit has a positive and significant effect on economic growth. In contrast, tax revenue and labor force participation rate have a negative but insignificant effect. Simultaneously, all three variables influence economic growth in BRICS countries. These findings highlight the critical role of fiscal policy in supporting economic development in the region.